Genome damage in testicular seminoma patients seven years after radiotherapy. (November 2013) - Fucic, Aleksandra; Gamulin, Marija; Katic, Jelena; Milic, Mirta; Druzhinin, Vladimir; Grgić, Mislav
Abstract Purpose: Testicular seminoma cancer incidence has significantly increased over the last few decades, and although it is successfully treated by radiotherapy, long-term health risks are still unclear. The aim of the study was to show long-term genome damage in patients with seminoma after radiotherapy. Materials and methods: Chromosome aberration (CA) and micronucleus (MN) assays seven years after radiotherapy with a total dose of 25 Gy were conducted in 10 testicular seminoma patients aged 23–49 years and results were compared with 10 healthy control subjects matched for age and smoking status. Results: Although mean CA frequency did not deviate from control values, significantly increased frequencies of dicentrics, double minutes, and ring chromosomes were detected in seminoma patients. MN frequency in binuclear lymphocytes of patients was similar to controls (4.60/1000 vs. 5.82/1000, respectively). Significantly higher MN frequency was detected in mononuclear lymphocytes of patients than in controls (2.55/1000 vs. 0.73/1000, respectively). Average percentage of centromere-positive MN was 62.6% in seminoma patients. Conclusion: This study shows the persistence of unstable CA in seminoma patients seven years after radiotherapy and the relevance of long-term follow up. MN frequency in mononuclear lymphocytes was shown to be relevant biomarker of long-term genome damage.